Within-item strategy switching in arithmetic: a comparative study in children - Ardiale, Eleonore; Lemaire, Patrick (Frontiers in Psychology, 2013)
The present study investigated age-related differences in children’s within-item strategy switching. Third, fifth, and seventh graders performed a computational estimation task in which they had to provide the better estimates to two-digit addition problems (e.g., 34+57) while using the rounding-down (e.g., 30+50) or the rounding-up strategy (e.g., 40+60). After having executing the cued strategy (e.g., 30+50) during 1,000 ms, participants were given the opportunity to switch to another better strategy (e.g., 40+60) or to repeat the same strategy. The results showed that children switched strategies within items, and were able to switch more often when the addition problems were cued with the poorer strategy than when cued with the better strategy. As they grew up, children based their decisions to switch strategies more often on whether the 1,000-ms strategy execution concerned the better strategy or a resource-consuming strategy (i.e., the rounding-up strategy). These findings have important implications to further understand mechanisms underlying within-item strategy switching as well as strategic variations in children.